Defective neuronal development in the mushroom bodies of Drosophila Fragile X Mental Retardation 1 Mutants. - Michel, C.I.; Kraft, R.; Restifo, L.L. (Journal of Neuroscience, 2004)
Fragile X mental retardation 1 (Fmr1) is a highly conserved gene with major roles in CNS structure and function. Its product, the RNA-binding protein FMRP, is believed to regulate translation of specific transcripts at postsynaptic sites in an activity-dependent manner. Hence, Fmr1 is central to the molecular mechanisms of synaptic plasticity required for normal neuronal maturation and cognitive ability. Mutations in its Drosophila ortholog, dfmr1, produce phenotypes of brain interneurons and axon terminals at the neuromuscular junction, as well as behavioral defects of circadian rhythms and courtship. We hypothesized that dfmr1 mutations would disrupt morphology of the mushroom bodies (MBs), highly plastic brain regions essential for many forms of learning and memory. We found developmental defects of MB lobe morphogenesis, of which the most common is a failure of beta lobes to stop at the brain midline. A similar recessive beta-lobe midline-crossing phenotype has been previously reported in the memory mutant linotte. The dfmr1 MB defects are highly sensitive to genetic background, which is reminiscent of mammalian fragile-X phenotypes. Mutations of dfmr1 also interact with one or more third-chromosome loci to promote alpha/beta-lobe maturation. These data further support the use of the Drosophila model system for study of hereditary cognitive disorders of humans.